Influence of Static Navigation Technique on the Accuracy of Autotransplanted Teeth in Surgically Created Sockets - Riad Deglow, Elena; Lazo Torres, Nayra Zurima; Gutiérrez Muñoz, David; Bufalá Pérez, María; Galparsoro Catalán, Agustín; Zubizarreta Macho, Álvaro; Abella Sans, Francesc; Hernández Montero, Sofía (My University, 2022)
The aim of this study was to analyse and compare the position of single¿rooted autotransplanted teeth using computer¿aided SNT drilling and conventional freehand (FT) drilling, by comparing the planned and performed position at the coronal, apical and angularlevel. Materials and methods: Forty single¿root upper teeth were selected and distributed into the following study groups: A. Autotransplanted tooth using the computer¿aided static navigation technique (SNT) (n = 20) and B. Autotransplanted tooth using the conventional free¿hand technique (FT) (n = 20). Afterwards, the teeth were embedded into two experimental models and 10 single¿root upper teeth were randomly autotransplanted in each experimental model. The experimental models were submitted to a preoperative cone¿beam computed tomography (CBCT) scan and a digital impression by a 3D intraoral scan, in addition to a postoperative CBCT scan, after the autotransplantation. Datasets from postoperative CBCT scans of the two study groups were uploaded to the 3D implant planning software, aligned with the autotransplantation planning, and the coronal, apical and angular deviations were measured. The results were analysed using Student¿s t¿test and Mann¿Whitney non¿parametric statistical analysis. Results: Coronal (p = 0.079) and angular (p = 0.208) statistical comparisons did not present statistically significant differences; however, statistically significant differences between the apical deviation of the SNT and FT study groups (p = 0.038) were also observed. Conclusions: The computer¿aided static navigation technique does not provide higher accuracy in the positioning of single¿root autotransplanted teeth compared to the conventional free¿hand technique. Keywords: accuracy; computed¿assisted template; computer¿aided static navigation; cone¿beam computed tomography scan; digital impression; tooth autotransplantation